Mitochondrial Small Heat Shock Proteins Are Essential for Normal Growth of Arabidopsis thaliana - Escobar, Mariela R.; Feussner, Ivo; Valle, Estela M. (Frontiers in Plant Science, 2021)
Mitochondria play important roles in the plant stress responses and the detoxification of the reactive oxygen species generated in the electron-transport chain. Expression of genes encoding stress-related proteins such as the mitochondrial small heat shock proteins (M-sHSP) is upregulated in response to different abiotic stresses. In Arabidopsis thaliana, three M-sHSPs paralogous genes were identified, although their function under physiological conditions remains elusive. The aim of this work is to uncover the in vivo function of all three M-sHSPs at the whole plant level. To accomplish this goal, we analyzed the phenotype, proteomic, and metabolic profiles of Arabidopsis knock-down lines of M-sHSPs (single, double, and triple knock-down lines) during normal plant growth. The triple knock-down plants showed the most prominent altered phenotype at vegetative and reproductive stages without any externally applied stress. They displayed chlorotic leaves, growth arrest, and low seed production. Concomitantly, they exhibited increased levels of sugars, proline, citric, malic and ascorbic acid, among other metabolites. In contrast, single and double knock-down plants displayed a few changes in their phenotype. A redundant function among the three M-sHSPs is indicated by the impairment in vegetative and reproductive growth associated with the simultaneous loss of all three M-sHSPs genes. The triple knock-down lines showed alteration of proteins mainly involved in photosynthesis and antioxidant defense compared to the control plants. On the other hand, heat stress triggered a distinct cytosolic response pattern and the upregulation of other sHSP members, in the knock-down plants. Overall, depletion of all three M-sHSPs in Arabidopsis severely impacted fundamental metabolic processes, leading to alterations in the correct plant growth and development. These findings expand our knowledge about the contribution of organelle-specific M-sHSPs to healthy plant growth under non-stress condition.